EFEKTIVITAS PENERAPAN JALUR SATU ARAH PADA KAWASAN PEMERINTAHAN DAN PERDAGANGAN DI KOTA BIMA-NTB - Eti Kurniati; Dedy Dharmawansyah (Program Studi Informatika Universitas Teknologi Sumbawa, 2019)
The implementation of one-way roads in the city of Bima began to be tested in 2017 ago. There are two main roads used as test material, one of which is on the Soekarto Hatta road along 5 Km and is a national road. This is done because of the increasing number of private vehicles used by the community and the number of traffic jams and traffic accidents on several roads. The area in the Soekarno Hatta route is included in a dense area because it is a central office and trade area. The purpose of this study is to look at the level of effectiveness of the implementation of the one-way lane by using several research methods, namely the analysis of the level of road service, queuing opportunities, vehicle actual speed and vehicle travel time. Based on the results of the analysis conducted, it is found that the level of road service is at level E (traffic starts to jam and low speed). In addition, the actual speed of the vehicle can be traveled at speeds of 48km / h with a travel time of 19.40 minutes. This indicates that the implementation of oneway lanes in the City of Bima has been effectively carried out.